Motion capture sensing techniques used in human upper limb motion: a review - Yahya, Muhammad; Shah, Jawad Ali; Abdul Kadir, Kushsairy; Mohd Yusof, Zulkhairi; Khan, Sheroz; Warsi, Arif (Emerald Publishing Limited, 2019)
Purpose Motion capture system (MoCap) has been used in measuring the human body segments in several applications including film special effects, health care, outer-space and under-water navigation systems, sea-water exploration pursuits, human machine interaction and learning software to help teachers of sign language. The purpose of this paper is to help the researchers to select specific MoCap system for various applications and the development of new algorithms related to upper limb motion.